Formation of Hermeneutic Competence of Managers of International Affairs - Davydova, Zh. (Problems of Engineer-Pedagogical Education, 2018)
The article grounds the topicality of the problem of hermeneutic competence formation for future managers of foreign economic affairs in the educational process of a university. The peculiarities of future specialists’ activity are reviewed. The objective factor lies in the increase of information volumes and transfer to information economy. This determines the necessity of formation of corresponding competencies to provide competitiveness at the labor market and effectiveness in the professional activity. These peculiarities determine the acuteness of transformation of current educational process on training managers of foreign economic affairs, adapted to new conditions. Its task is formation of a specialist’s professional competence which is based on the ability to work effectively with information and to interpret it. Analysis of the current situation demonstrated that not enough attention is paid to the task of forming hermeneutic competence. The contradictions are determined, solving of which makes the problem actual.